Effect of proanthocyanidins on blood pressure: A systematic review and meta-analysis of randomized controlled trials. (March 2021) - Ren, Jingyi; An, Jiaqi; Chen, Mengyuan; Yang, Haiyue; Ma, Yuxia
Graphical abstract: Abstract: Background: Hypertension is a common chronic disease that can lead to serious health problems. Previous studies have not drawn a consistent conclusion about the effect of proanthocyanidins (PCs) on blood pressure (BP). This systematic review and meta-analysis aims to evaluate the effect of PCs supplementation on blood pressure (BP). Methods: A comprehensive literature search was performed in 6 databases (Pubmed, Scopus, ISI Web of Science, the Cochrane Library, Embase and Google Scholar) to identify the randomized controlled trials (RCTs) that evaluated the BP-lowering effect of PCs. Subgroup and sensitivity analyses were conducted to evaluate the potential heterogeneity. Meta-regression analysis was used to evaluate dose effects of PCs on BP. Results: A total of 6 studies comprising 376 subjects were included in our meta-analysis to estimate the pooled effect size. This meta-analysis suggested that PCs supplementation could significantly reduce systolic blood pressure (SBP) (WMD: -4.598 mmHg; 95 % CI: -8.037, -1.159; I 2 = 33.7 %; p = 0.009), diastolic blood pressure (DBP) (WMD: -2.750 mmHg; 95 % CI: -5.087, -0.412; I 2 = 0.0 %; p = 0.021) and mean arterial pressure (MAP) (WMD: -3.366 mmHg; 95 % CI: -6.719, -0.041 mmHg; I 2 = 0.0 %; p = 0.049), but had no significant effect on pulse pressure (PP) (WMD: -2.131 mmHg; 95 % CI: -6.292, 2.030; I 2 = 0.0 %; p = 0.315). When the studies were stratified according to the duration of the study, there was a significant reduction on SBP in the subset of the trials with <12 weeks of duration. On the contrary, there was a significant reduction on DBP in the subset of the trials with ≥12 weeks of duration. The Subgroup analysis by BMI indicated that a significant reduction on SBP for people with a higher BMI (BMI ≥ 25) and a significant reduction on DBP for people with a lower BMI (BMI < 25). Additional subgroup analysis revealed low-dose-PCs (<245 mg/day) could significantly reduce SBP, DBP and MAP. The meta-regression analyses did not indicate the dose effects of PCs on SBP, DBP, PP and MAP. Conclusion: Based on the current findings, PCs supplementation may be a useful treatment of hypertensive patients as well as a preventive measure in the prehypertensive and healthy subjects. However, further investigation is needed to confirm these results.